Socio-demographic characteristics and smoking pattern of smokers seeking care in cessation programs - De Souza Leal, Alice Cristine [UNESP]; Silveira, Ana Clara [UNESP]; Freire, Ana Paula Coelho Fiqueira [UNESP]; Santos, Ana Paula Soares [UNESP]; Ramos, Dionei [UNESP]; Ramos, Ercy Mara Cipulo [UNESP]; Uzeloto, Juliana Souza [UNESP]; De Melo Dantas, Vanessa [UNESP]; De Oliveira, Gabriela Martins [UNESP] (Centro Universitario Sao Camilo - Sao Paulo, 2017)
Knowing the characteristics of smokers is essential to adequately structure tobacco cessation programs in order to meet the specific needs of this population. To analyze socio-demographic characteristics and the smoking pattern of smokers seeking care in cessation programs. A 38-month retrospective analysis of data from the initial evaluation of smokers who sought the Anti-Smoking Counseling and Orientation Program of UNESP-Presidente Prudente was conducted. The sample consisted of 209 women and 150 men aged 48.16 ± 12 years; 34% did not complete high school or university, 38.44% presented a high level of dependence, and 72.15% presented themselves in the motivational phase of contemplation. In this study, some characteristics of smokers seeking specialized care for smoking cessation were evidenced. These findings will facilitate the approach by professionals who work with this theme, allowing for better targeting in the treatment and consequently an increase in the smoking cessation success rate of this population.
Características sociodemográficas e padrão de consumo tabagístico de fumantes que procuram atendimento em programas de cessação
Keywords: Nicotine; Smoking; Tobacco